Analysis of changes in waste generation and management in Poland against the background of EU waste management objectives - Dziawgo, Ewa (Analiza zmian ilości wytwarzanych i zagospodarowywanych odpadów w Polsce na tle założeń UE w zakresie gospodarki odpadami, 2022)
One of the environmental problems of the current generation is the increase in volume of waste generated, which has a negative impact on the environment and human health. Therefore, it is important to reduce the amount of waste generated and to manage it rationally. Waste management is one of the areas of environmental protection. The article examines the changes in the amount and structure of waste generated in Poland in the period 2017-2020. An analysis of the size and structure of funding sources of the main forms of waste management was also carried out. The aim of the article was to present, compare and evaluate the changes occurring in waste management and its sources of financing. The research considered the impact of the Covid-19 pandemic on the volume of waste generated and on waste management. The analysis shows that the crisis caused by the Covid-19 pandemic affected the decrease in the volume of total waste generated and the increase in the volume of municipal waste. There was also some variation in the area of generated waste and its management in individual provinces.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2022; vol. 66, nr 4, s. 41-56
Keywords: waste; waste management; municipal waste; industrial waste; odpady; gospodarka odpadami; odpady komunalne; odpady przemysłowe